1975
DOI: 10.1111/j.1365-2818.1975.tb04063.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of biological molecules, macromolecules and cells

Abstract: Cathodoluminescence observations on biological compounds are compared with previously established data from ultra violet and visible light excitation studies. The comparison demonstrates that the same molecules are responsible for the luminescence properties of macromolecules independent of the type of exciting radiation. Natural cathodoluminescence was also observed from cells. Moreover, advantages gained by the absorption of strongly cathodoluminiscent dyes into cells are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Generally, SEM samples are sputter-coated with gold/palladium (or similar metals) to avoid a charge build-up on the sample surface and subsequent saturation of the electron detector. However, like other workers [18, 19, 20], we have noted almost complete loss of fluorescence with a 60-second gold/palladium coating. We found that a 15-second sputter coating passes at least 50% of the maximum fluorescence.…”
Section: Sample Preparationsupporting
confidence: 90%
“…Generally, SEM samples are sputter-coated with gold/palladium (or similar metals) to avoid a charge build-up on the sample surface and subsequent saturation of the electron detector. However, like other workers [18, 19, 20], we have noted almost complete loss of fluorescence with a 60-second gold/palladium coating. We found that a 15-second sputter coating passes at least 50% of the maximum fluorescence.…”
Section: Sample Preparationsupporting
confidence: 90%
“…Organic molecules, which comprise up to 3% of conodont elements (Zhuravlev, 2023), may make some contribution to CL. Pure hydroxyapatite (HAP) has a grey or reddish CL, but pure collagen has a bluish-green CL (Barnett et al, 1975;Roman-Lopez et al, 2014). In RGB coordinates, the CL of all tissues of unaltered conodont elements is close to that of HAP and different from that of pure collagen (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis of the functional units is performed by electron microscopy, and the relationships between the structures and their functions are investigated. The CL imaging, using a scanning electron microscope (SEM), can resolve the limitation of the spatial resolution, which is restricted by the Rayleigh criterion. Imaging of the organic compounds, such as synthetic dyes and biological materials, has been challenged using CL. Therefore, the development of a organic luminescent probe with high emission efficiency and high electron irradiation tolerance is expeditiously demanded.…”
Section: Introductionmentioning
confidence: 99%